Ultrasound-Guided Extracorporeal Shock Wave Lithotripsy of Pancreatic Ductal Stones: Six Years’ Experience - Werner Johanns; Christian Jakobeit; Lucas Greiner; Jan Janssen (Canadian Journal of Gastroenterology)
Extracorporeal shock wave lithotripsy (ESWL) and endoscopic sphincterotomy (EST) was performed in 35 patients suffering from pancreatic duct stones. Calculi disintegration and resolution of obstruction were achieved in all cases. Completely stone-free ducts were achieved in 16 patients (46%) while some peripheral asymptomatic stone material remained in 19 (54%). Dilation of the main pancreatic duct was reduced in 29 patients (83%). Twelve patients (34%) became completely asymptomatic and 17 (49%) reported a marked reduction of pain. Pancreatogenic steatorrhea ceased and 18 patients (51%) gained weight. Pathological glucose tolerance returned to normal in one patient. No major complications were observed. The combination of ESWL and EST is a successful, nonoperative, new treatment in pancreatic stone disease.